The symptomatic behaviour screening tool (symbest) for early identification of developmental delays among children age 3-4. - Arumugam, Shyielathy; Eng Hock, Kway; Mohamed Isa, Zainiah@Zaniah (Jurnal Pendidikan Bitara UPSI, 2019)
This article suggests that developmental screening, especially for behaviour symptoms, should be promptly addressed and the practice must be introduced in the early childhood education programs to reach a justified consensus between the primary care practitioners and the school system. Given that, the primary of this research is to develop a symptomatic behaviour screening tool (SymBest) for early childhood educators to identify children with symptomatic behaviours. The design and development process of SymBest is based on the theory of maturation and the theory of cognitive development along with developmentally appropriate framework (DAP). Fuzzy Delphi analysis was conducted with 18 participants from diverse backgrounds of clinical and education to gain the expert consensus on the suitability of the constructs and items representing SymBest. The findings showed that the experts have a fair degree of agreement on the constructs and the items suggested to form SymBest. The constructs and items with accepted threshold value, percentage of group consensus and fuzzy score are then organised in sequence priority to form the screening tool.